Nonperturbative quark, gluon, and meson correlators of unquenched QCD - Cyrol, Anton Konrad; Pawlowski, Jan M.; Mitter, Mario; Strodthoff, Nils (Physical review, 2018)
We present nonperturbative first-principle results for quark, gluon, and meson 1PI correlation functions of two-flavor Landau-gauge QCD in the vacuum. These correlation functions carry the full information about the theory. They are obtained by solving their functional renormalization group equations in a systematic vertex expansion, aiming at apparent convergence. This work represents a crucial prerequisite for quantitative first-principle studies of the QCD phase diagram and the hadron spectrum within this framework. In particular, we have computed the gluon, ghost, quark, and scalar-pseudoscalar meson propagators, as well as gluon, ghost-gluon, quark-gluon, quark, quark-meson, and meson interactions. Our results stress the crucial importance of the quantitatively correct running of different vertices in the semiperturbative regime for describing the phenomena and scales of confinement and spontaneous chiral symmetry breaking without phenomenological input.